2012
DOI: 10.1002/hyp.9224
|View full text |Cite
|
Sign up to set email alerts
|

Drainage network detection and assessment of network storage capacity in agrarian landscape

Abstract: Drainage networks in agrarian landscape withinfloodplains constitute surface’s discontinuities that are expected to affect hydrological response during floods. Drainage network recognition and quanti fi cation of water storage capacity within channels are, therefore, crucial for watershed planning and management. These evaluations require accurate spatial information for the area of interest and in most cases, when studying large catchments, broad datasets of ditches locations and descriptions are not availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 21 publications
0
89
0
1
Order By: Relevance
“…Since drainage networks in agrarian landscapes within floodplains are expected to affect hydrological response during floods (Cazorzi et al, 2013) channel storage capacity can i) outline areas whose hydrological behavior is potentially critical during floods, where land use might increase the level of risk, and ii) they allow to identify storage volumes already available on the surface that can contribute to laminate flood peaks. Therefore this work provides an additional proof of suitability of the estimated network parameters (drainage density and storage capacity) in supporting flood management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since drainage networks in agrarian landscapes within floodplains are expected to affect hydrological response during floods (Cazorzi et al, 2013) channel storage capacity can i) outline areas whose hydrological behavior is potentially critical during floods, where land use might increase the level of risk, and ii) they allow to identify storage volumes already available on the surface that can contribute to laminate flood peaks. Therefore this work provides an additional proof of suitability of the estimated network parameters (drainage density and storage capacity) in supporting flood management.…”
Section: Discussionmentioning
confidence: 99%
“…At first, a semi-automatic approach, developed by Cazorzi et al, 2013, has been applied in order to identify the minor drainage network system and estimate some its parameters such as drainage density and storage capacity, through the DTM which dates back to 2006 and a morphological parameter named Relative Elevation Attribute (REA) derived from it. A thresholding approach based on the standard deviation of REA has been used in order to automatically extract the small-scale topography features (minor drainage network system) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brummer and Montgomery, 2003;Wohl, 2004;Sofia et al, 2015), and channel networks are identified to evaluate hydrological responses in floodplains (e.g. Cazorzi et al, 2013). Continuous measures such as curvature can arguably distinguish dominant geomorphic processes (e.g.…”
mentioning
confidence: 99%